NASEHAT SEBAGAI MOTIVASI BELAJAR DI ERA DIGITAL PERSPEKTIF ALQURAN DAN HADITS - Reni Puspita Sari; Dwi Ratnasari; Hidar Amaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Motivation to learn includes the enthusiasm possessed by individuals, both originating from internal themselves and from external factors. The important role of advice as a source of motivation in facing learning challenges in the digital era is an encouragement for students to be active in learning by using technology wisely. This research aims to understand the challenges of learning motivation in the digital era and how advice is implemented in digital learning. The research method used is descriptive qualitative with a focus on library research, namely the study of literature as a research subject. The research results indicate that the challenges of learning motivation in the digital era include the tendency to like freedom, high dependence on the internet and social media, the tendency for students to be lazy, less good at socializing, and less attention to togetherness values such as mutual cooperation. Apart from that, there is a tendency for free behavior, westernized orientation, and a lack of attention to ethics, formal rules, customs, and manners. In facing these challenges, implementing advice as learning motivation involves providing digital literacy insights to students, including digital skills, digital ethics, digital security, and digital culture. Advice is also given to prevent deviations in the use of social media, which can cause students to become too dependent on gadget devices and forget about learning activities.